Dialectic of Urban and Rural in Modern Japanese Society Portrayed on Kimi no Na Wa (Your Name) by Makoto Shinkai - Varel Dava Chrisna Widya Putra Pratama; Rahayu Puji Haryanti (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study applies the theory of cultural materialism to explore the dialectical relationship between urban and rural life in modern Japanese society, as portrayed in Makoto Shinkai’s animated film Kimi no Na Wa (Your Name). Grounded in Marvin Harris’ theoretical framework, which emphasizes the interrelation of infrastructure, structure, and superstructure in shaping cultural expression, the research investigates how the narrative constructs, critiques, and reimagines rural-urban dynamics. Employing a descriptive qualitative approach, the study conducts content and thematic analysis of selected quotations, character dialogues, and symbolic scenes. The findings reveal that Kimi no Na Wa represents the fictional village of Itomori as a rural space rooted in spiritual continuity, familial hierarchy, and environmental constraints, while Tokyo is depicted as a technologically advanced, secular, and emotionally distant urban center. The film’s metaphysical and symbolic narrative structure critiques socio-economic disparities and the erosion of traditional values, ultimately suggesting a synthesis between rural and urban identities. The study concludes that Kimi no Na Wa serves both as a cultural mirror and critique, reflecting the shifting socio-cultural landscape of Japan through the lens of cultural materialism. The research offers a novel contribution by demonstrating how Japanese animated media can be interpreted as a site of cultural negotiation and resistance within material and ideological frameworks.